TELAAH KONSTITUSIONAL PENGATURAN IMPEACHMENT PRESIDEN DAN WAKIL PRESIDEN DALAM MEWUJUDKAN DEMOKRASI - J Sahalessy (Faculty of Law, Universitas Pattimura, 2015)
The President as the holder of power operation of the Republic of Indonesia as mandated by the 1945 constitution, have full responsibility in the case of the head of state and head of government. In running the government, the president is assisted by a vice president. When the president and vice president elected directly by the people in a general election is considered to be incapable of running the state government for reasons that have been determined by the 1945 Constitution, the legislative body that oversees the running of the government led by the president can give a confidence vote in the name parliament is then submitted to the judiciary in this case the Constitutional Court to decide the president and / or vice president deserves to be dismissed from office or not, and then a plenary session of People's Consultative Assembly (MPR), which is a combination of DPR and DPD to determine the dismissal of the President from office. Of course, the President of Indonesia dismissal mechanism which implicitly specified in the 1945 Constitution states that when the president removed from office, the Vice President also dismissed as